Implementation ISO 9000 study on contractor firm in Malaysia - Noor Syuhada, Inche Md. Shamsuddin (2018)
ISO 9000 is an international standard intended to provide the generic core of a quality system standard applicable to a broad range of industries and economic sectors. The purpose of the standard the ISO form is to promote the development of standards in exchange facilitate of international goods or services and to promote cooperation in the form of intellectual, scientific, technological and economic activities. If re-scanned, the project results have been done by the contractor getting the ISO 9000 certification will add confidence to the client side because the contractor has guidelines on standards the quality that they are supposed obey. Indirectly, the contractor which is recognized by ISO 9000 will have the opportunity and be able to compete in local or international markets to get mega projects such as hydroelectric hydro projects or projects abroad.The objective of the study are to study the importance of ISO 9000 recognition obtained by the contractor firm, to design a questionnaire about the benefit and barrier faced by contractors during the implementation of ISO 9000, to analyse the study on implementation of ISO 9000 on contractor firm in Malaysia. This study has been focusing on the implementation of ISO 9000 on Malaysian contractors for look at the objectives previously stated. The methodology for this research was conducted in survey research. The methods used are literature review, questionnaire survey, and average index. This literature provided information from journal, book, and newspaper. Then, use do questionnaire to obtain data and use average index to process data. From the data collected, there are 100 respondent has been send the questionnaire but only 50 respondent answer the questionnaire. From the survey of the questionnaire, it shows that respondent want to improve quality awareness at their firm from the certification. Furthermore, they need to cooperate with the new way of work from the application of the system.